Education and globalization. Society and the knowledge economy - Esteve Zarazaga, José Manuel (Avances en Supervisión Educativa, 2009)
The purpose of this article is to offer a reflection on the profound social changes undergone in the last years and on the great transformations undertaken by European educational systems in an still unfinished process to adapt themselves to a real avalanche of changes that occurred at the end of the 20th century: in politics, in economy, in production structures, in moral values and private lifestyle, in the patterns for the relationship between the younger generation and the one of adults, in the presence and influence of the media, in the permanent evolution of international relationships, especially in situations concerning the disappearance of the so-called socialist block of countries, the movement of non-aligned countries, or the lack of a unique sense for expressions such as "the Arab countries", "the working class" or "Capitalism".